ANALISIS PENGARUH ERUBAHAN TINGKAT SUKU BUNGA SBI DAN PERUBAHAN KURS US TERHADAP HARGA PASAR SAHAM SEMEN GRESIK, TBK PERIODE JANUARI 2002 – DESEMBER 2006 - Oktafalia Marisa; Maya Syafriana (Universitas Bunda Mulia, 2017)
Investment climate has begun to rise since a few years ago. Stock price fluctuations keep stable and move to the positive position. Stock price fluctuation affected by two factors, internal factors and external factors. Internal factors consist of company’s cash flow, dividend and investment behaviour. External factors consist of monetary policy, exchange rate, interest volatility, globalization, companies’ competition, and technology. This research, try to find out the effects of SBI rate and exchanged rate (USD/Rp) to PT. Semen Gresik’s stock price. Keywords : Investment, stock price, SBI’s rate, and Exchanged rate.